2016
DOI: 10.1039/c4dt00399c
|View full text |Cite
|
Sign up to set email alerts
|

Towards a full understanding of the nature of Ni(ii) species and hydroxyl groups over highly siliceous HZSM-5 zeolite supported nickel catalysts prepared by a deposition–precipitation method

Abstract: Highly siliceous HZSM-5 zeolite supported nickel catalysts prepared by a deposition-precipitation (D-P) method were characterized by Fourier transform infrared (FT-IR), hydrogen temperature programmed reduction (H2-TPR), X-ray diffraction (XRD), N2-absorption/desorption, field emission scanning electron microscopy (FE-SEM), X-ray photoelectron spectroscopy (XPS), and (27)Al magic-angle nuclear magnetic resonance (MAS NMR) techniques. The results showed that the D-P of nickel species occurred predominantly on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 82 publications
3
14
1
Order By: Relevance
“…There are two possible interpretations of these peaks. First, these peaks can be attributed to the presence of nickel phyllosilicate species, as was suggested previously [37, 39,40]. Generally, nickel phyllosilicate is not observed by XRD probably due to its very high dispersion.…”
Section: Catalyst Characterizationsupporting
confidence: 56%
“…There are two possible interpretations of these peaks. First, these peaks can be attributed to the presence of nickel phyllosilicate species, as was suggested previously [37, 39,40]. Generally, nickel phyllosilicate is not observed by XRD probably due to its very high dispersion.…”
Section: Catalyst Characterizationsupporting
confidence: 56%
“…For calcined samples the micropore volume slightly decreases with nickel loading, while mesopore volume increases; thus indicating that micropores are being blocked by the nickel particles, and that the nickel species present after calcination lead to the formation of additional mesopores. This phenomenon was described by Chen et al who related the presence of defects in the HZSM-5 with the formation of nickel phyllosilicates and attributed the development of mesopores to the aggregation of these defects [14]. After reduction, Ni 2+ species are reduced to Ni metal and the trends are no longer evident.…”
Section: Textural Propertiesmentioning
confidence: 74%
“…More recent studies have characterized the nickel phyllosilicate species [12,13]. In a recent work by Chen et al [14], they have confirmed the existence of and characterized nickel hydroxide, nickel oxide, and 1:1 and 2:1 nickel phyllosilicate species present in Ni/HZSM-5 catalyst prepared by depositionprecipitation.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The absence of peaks for NiPS is probably because of the low crystallinity of NiPS. It has been reported that the crystal structure of NiPS is easily affected by the preparation and calcination environment . Previously, it was shown to be common that NiPS prepared by the same ammonia evaporation method showed different XRD patterns .…”
Section: Resultsmentioning
confidence: 99%